2003
DOI: 10.1034/j.1600-051x.2003.300203.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of gingivitis with hyaluronan

Abstract: These data suggest that a hyaluronan containing gel has a beneficial effect in the treatment of plaque-induced gingivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 36 publications
10
97
0
7
Order By: Relevance
“…Jentsch et al in their study found that adjunctive application of hyaluronon significantly reduced gingivitis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Jentsch et al in their study found that adjunctive application of hyaluronon significantly reduced gingivitis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronan gel is also effective in controlling inflammation and gingival bleeding, as shown by a study of Mesa et al that documented reduction in the depth of gingival pockets along with a significant decrease in epithelial and lymphocyte cell proliferation after the use of HA gel [384]. Similarly, 0.2 % hyaluronan containing gel has a benefic effect on the treatment of plaque induced gingivitis due to the significant decrease in peroxidase and lysozyme activities [383]. In addition, De Arau'jo Nobre found that HA and chlorhexidine maintain a healthy perimplant complex in immediate function implants for complete rehabilitations in the edentulous mandible [385].…”
Section: Proteins and Poly(amino Acids)mentioning
confidence: 89%
“…Pistorius et al evaluated the efficacy of topical application of HA for treatment of gingivitis and found that HA containing preparations are a useful adjunct in the anti-gingival therapy [382]. A commercialized gel formulation, Gengigel ® (Ricerfarma S.r.l., Milano, Italy), contains high molecular weight 0.2 % fractions of HA , for its effect in the treatment of plaque induced gingivitis as an adjunct [383]. Hyaluronan gel is also effective in controlling inflammation and gingival bleeding, as shown by a study of Mesa et al that documented reduction in the depth of gingival pockets along with a significant decrease in epithelial and lymphocyte cell proliferation after the use of HA gel [384].…”
Section: Proteins and Poly(amino Acids)mentioning
confidence: 99%
See 1 more Smart Citation
“…HA has an anti-inflammatory effect acting as a scavenger which drain, metalloproteinases, prostaglandins and others which promote inflammatory activities (24) . The anti-edematous property of HA also may be related to its osmotic properties (25) . HA regulates the inflammatory and immune response acting as an anti-oxidant so, HA may stabilize the granulation tissue matrix (26) .…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%